Associations between urate levels and amyotrophic lateral sclerosis functional score with edaravone treatment: Post hoc analysis of studies MCI186‐16, MCI186‐17, and MCI186‐19. Issue 5 (2nd September 2022) - Takahashi, Fumihiro; Kano, Osamu; Nagano, Yoshito; Yoneoka, Takatomo; Nelson, Sally; Ushirogawa, Yoshiteru
Abstract: Introduction/aims: Edaravone in amyotrophic lateral sclerosis (ALS) was analyzed in two phase 3 studies (MCI186‐16 and MCI186‐19). Those trials enrolled patients with Japanese ALS severity grades 1 and 2 (less severe ALS), but many patients progressed to grades 3 and 4 during the double‐blind treatment period. The placebo patients who initiated edaravone treatment in the open‐label periods provided an opportunity to assess the effects of edaravone in more severe ALS. This study also assessed the association between ALS Functional Rating Scale‐Revised (ALSFRS‐R) slope and biomarker changes after open‐label edaravone initiation. Methods: Change in ALSFRS‐R slope in placebo patients before and after initiating edaravone treatment was assessed using the random coefficient model. The association of ALSFRS‐R change and blood marker changes was explored by the least absolute shrinkage and selection operator (LASSO) method of machine learning. Results: Twenty‐four percent of patients (35/146) in the placebo‐edaravone group showed ≥25% slowing of decline in the ALSFRS‐R slope. Within the 25% slower‐decline group, 60% (21/35) had Japanese ALS severity grades 3 or 4 at the start of edaravone treatment. The LASSO model identified serum urate as associated with the percentage change in ALSFRS‐R slope. The rate of decrease in urate was smaller in the 25% slower‐decline group than in the non‐25% slower‐decline group during edaravone treatment. Discussion: This post hoc analysis indicated that ALS patients, including those with advanced ALS severity grades, may receive benefit in the group of patients whose urate levels are stable during the course of the edaravone treatment.